Efeito do quiabo (Abelmoschus esculentus), como suplemento dietético, sobre disfunções metabólicas induzidas por redução de ninhada em ratos - Ricken, Camila Luiza Rodrigues dos Santos (2021)
Over nutrition in the early stages of life is considered a predisposing factor for the development of obesity in adulthood. Bioactive agents present in functional foods have been constantly considered for their beneficial effects in the treatment of metabolic diseases resulting from obesity. The present study evaluated the effect of diet supplemented with okra, Abelmoschus esculentus (AE), on energy metabolism and glucose homeostasis of rats induced to obesity during lactation. At day 3rd of life, litters were standardized to 3 pups (small litter, SL), while the normal litter (NL) was adjusted to 8 rats. On days 6th, 11 th and 16th of life, milk intake was measured and on day 12th of lactation, milk samples were collected. At weaning (22 days old), groups were subdivided into: NL-SD and SL-SD, rats fed standard diet, and NL-AE and SL-AE, rats fed diet supplemented with 1.5% okra. Body weight, food and water intake were measured every two days. From 90 days of age, glucose tolerance (ipGTT) and central insulin sensitivity (10-3mmol/L) tests were performed, subsequently, the rats were euthanized for removal of the hypothalamus, fat stores, lean mass, and blood collection. There was no statistical difference regarding body weight of SL versus NL mothers during lactation (P>0.05). As for water and food intake, it was observed a reduction of 35.04% and 38.91% (P<0.01), respectively. Regarding feed efficiency, an increase of 97.22% was observed in SL mothers (P<0.05) and an increase of 81% in weight gain of SL mothers compared to NL (P<0.05). Was observed an increase in total cholesterol (23.76%), triglycerides (12.48%), fat content (37.06%) and total energy content (35.51%) in milk from SL rats (P<0.05). Compared to NL-SD, SL-SD rats showed obese phenotype (higher body weight, 10.24%, and adiposity index, 31.75%, P<0.05), as well as showed hypertriglyceridemia, hyperglycemia, and glucose intolerance during ipGTT (P<0.05); on the other hand, supplementation with EA attenuated these parameters (P<0.05), resembling NL-SD rats. Compared to NL-SD rats, in SL-SD rats, increased hypothalamic levels of TNF-α (43.51%), IL-6 (78.49%), and IL-1β (50.13%, P<0.05) were observed, in addition to hyperphagia in SL-SD rats compared to SL-AE (31.5%, P<0.05). On the other hand, ingestion of okra attenuated the expression of TNF-α (-37.39%), IL-6 (- 37.73%) and IL-1β (-39.96%) in SL-AE versus SL-SD rats (P<0.05), also affecting the reduction of food intake by -22.77% compared to SL-SD (P<0.05). The central effect of insulin led NL-SD and NL-AE rats to reduce food intake during the first 4 hours of the test (-19.77%, P<0.05); whereas this effect was not observed in SL rats (P>0.05). We conclude that dietary supplementation with 1.5% okra prevents the development of obesity and glucose intolerance in early overfed rats, a fact that may be associated with improvement in the degree of hypothalamic inflammation and central insulin resistance.